Characteristics of Pelvic Fracture in the Cat - Bookbinder, P. F.; Flanders, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
The medical records from 103 cats with pelvic fracture were studied retrospectively. Most cats were 12 months of age or younger and both sexes were equally represented. The majority of the cats had been hit by a car. Numerous combinations of fracture types were present, but more than half involved combination of pelvic floor fractures with ilial body fracture, ilial body fracture contralateral to a sacroiliac luxation, a unilateral sacroiliac luxation, or bilateral sacroiliac luxation. The majority of cats had one or more serious extrapelvic injuries, the most common being sacral fracture, disruption of the coxofemoral joint, femoral fracture, and peripheral nerve paresis. Statistically significant positive association was found for ischiatic nerve injury and ipsilateral ilial body fracture alone and in combination with other fractures, and for ischial body fracture and sacral body injury. A negative or “protective” association was found between sacroiliac luxation and ipsilateral coxofemoral injury.A retrospective study of 103 pelvic fractures in cats was done. More than 50% of the cats had pelvic floor fractures in combination with unilateral ilial body fractures, unilateral sacroiliac luxations, bilateral sacroiliac luxations, or contralateral ilial body fracture and sacroiliac luxation. Common extrapelvic injuries included sacral fracture, coxofemoral joint injury, femoral fracture, and peripheral nerve paresis.
Keywords: Cat; pelvic fracture; coxofemoral; sacroiliac luxation